AAK aims to support low-GHG-emissions development through a variant of the ACE calculator - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
One of AAK's sustainability ambitions is to support their clients with climate smart choices. For that, they adopt a variant of ACE; this stimulates them to better valorize side-streams.